On the influence of large-scale mantle irregularities on the daily Liava numbers - Lubkov, M. V. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2011)
On the base of original combined method, allowing to superpose analytical advantages of the Sasao, Okubo, Saito approach with computer possibilities of the finite element method it was carried out evaluation of influence of sub horizontal large-scale mantle heterogeneities about some thousands km long on the Love and Shida numbers of the second order for diurnal tides. It was shown that pre-sence of such mantle heterogeneities non linearly influences on the earth tidal parameters. And this influence on the diurnal Love and Shida numbers of the second order can reach a few percentages.